Chicken and rabbit antibodies against porcine pepsinogen A - Kulhavá, Lucie; Miarková, Eva; Přikryl, Petr; Hodek, Petr; Tichá, Marie; Kučerová, Zdenka (Prague medical report, 2015)
Isolated porcine pepsinogen A was used for the preparation of polyclonal rabbit and polyclonal chicken anti-pepsinogen A antibodies. Immunochemical properties of both immunoglobulin fractions were compared. The rabbit anti-serum was further purified using immobilized porcine pepsinogen A on magnetic cellulose beads and the resulting anti-pepsinogen A fraction proved to be applicable for the separation and the determination of porcine pepsinogen A. In contrary, antibodies prepared from chicken eggs by the same way have been found not suitable for the evaluation of the pepsinogen A level. Unexpectedly, the pre-immune fraction of chicken antibodies showed reactivity against porcine pepsinogen A and the affinity separation of specific polyclonal chicken anti-pepsinogen A antibodies on immobilized porcine pepsinogen A did not result in an enrichment of anti-pepsinogen A antibodies.
Keywords: Cattle; Pepsinogen A; kur domácí; Animals; skot; Enzyme-Linked Immunosorbent Assay; Rabbits; žaludeční sliznice; Chickens; Gastric Mucosa; Immunohistochemistry; prasata; Antibodies; Stomach Neoplasms; imunohistochemie; ELISA; Swine; nádory žaludku; králíci; zvířata; pepsinogen A; protilátky